Droit de la mer : La contribution du Canada au nouveau concept de la zone économique - Léger, Georges (Études internationales, 1980)
The decade-long process of negotiation leading to a new regime of Oceans Law is drawing to a close. One of its major achievements to date is the elaboration of an entirely new concept in ocean space, the exclusive economic zone. Canada has played a leading role in bringing about consensus on the main elements of this zonal approach, a bridge linking certain features of the territorial sea regime with a number of safeguards derived from the exercise of high seas rights.Canada 's contribution was based generally on a novel application of the functional approach which has been prevalent in Canada 's treatment of Law of the Sea issues over the past few years. The idea was to apply the principles of delegation of powers to those of functionalism, in order to foster a zonal approach whereby certain functional rights and obligations (pertaining, for instance, to fisheries or to the marine environment) would be carried out by the coastal state on behalf of the international community. In recognition of its exercise of this mandate, and in regard to its geographical proximity to the ocean space it managed, the coastal state would be granted a preferential (and for most purposes an exclusive) access to the resources of the zone. One of the best examples of this approach can be found in Canada 's earliest efforts to deal with the fundamental issue of fishing rights at the Conference. Bringing a multi-disciplinary focus to bear on the need to distinguish between different species of fish in the coastal areas, the Canadian delegation, with the co-sponsorship of a number of like-minded countries, brought forward proposals tailored to the management and exploitation of these species.